2008
DOI: 10.1302/0301-620x.90b2.19436
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of peri-prosthetic infection at the hip using triple-phase bone scintigraphy

Abstract: We evaluated triple-phase bone scintigraphy in the differential diagnosis of peri-prosthetic infection in 46 patients with a total hip replacement or bipolar hemiarthroplasty who were due for revision surgery. There were 18 men and 28 women, with a mean age at operation of 64.6 years (28 to 81). We defined peri-prosthetic infection as an increased uptake of radioisotope in all the phases of triple-phase bone scintigraphy and validated these results against the histological and/or microbiology results in every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 14 publications
(12 reference statements)
0
33
1
3
Order By: Relevance
“…The fact that only a minority of these patients underwent revision limits comparison to a true diagnostic gold standard. Another study reported a sensitivity of 88% and a specificity of 90% for 46 patients a mean of 8.5 years after hip arthroplasty (268).…”
Section: Imagingmentioning
confidence: 96%
“…The fact that only a minority of these patients underwent revision limits comparison to a true diagnostic gold standard. Another study reported a sensitivity of 88% and a specificity of 90% for 46 patients a mean of 8.5 years after hip arthroplasty (268).…”
Section: Imagingmentioning
confidence: 96%
“…2 and 3). Moreover, the data in the literature about its diagnostic efficiency show a considerable variability and to some extent, this inconsistency is caused by several factors, such as (1) the use of different scan interpretation criteria (quantitative analysis versus qualitative approach), (2) performing a three-phase study instead of only a delayed bone scan, (3) the type of prosthesis (knee versus hip, cemented versus cementless, old versus new ones) affecting both the degree and the pattern of periprosthetic bone uptake, and last but not least, (4) the fact that during the first year after implantation, when nearly two thirds of all PJIs occur, periprosthetic bony uptake is so variable that only a completely normal BS, which in clinical practice is uncommon, provides us useful information [10][11][12][13][14][15][16][17][18][19]. Nonetheless, BS is more sensitive than plain radiographs [20].…”
Section: Imaging Techniques and Featuresmentioning
confidence: 99%
“…In two of six patients with knee prostheses SPECT/CT correctly localized leucocyte uptake in the synovium and therefore could reliably exclude a PJI [76]. 18 F-Fluorodeoxyglucose positron emission tomography: current role in PJI In recent years, 18 F-fluorodeoxyglucose positron emission tomography (FDG PET) has been used successfully for assessing a multitude of malignant disorders. FDG, however, also accumulates at the sites of infection and inflammation, including those of the musculoskeletal system [77].…”
Section: Spect/ct Bone Leucocyte and Gallium Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genel olarak kabul edilen görüşe göre, perfüzyon, kan havuzu ve geç fazda periprostetik bölgede artmış tutulum olmaması enfeksiyon olmadığının güçlü bir kanıtıdır. Enfeksiyon tanısı için erken arteryel ve kan havuzu fazlarında patolojik tutulum olması pozitif bulgu iken, perfüzyonun artmadığı durumlarda aseptik gevşeme düşünülmelidir (29). Dinamik ve kan havuzu fazında artmış aktivite tutulumu ve geç görüntüde Tc-99m difosfonatın artmış metabolik aktivitesi ile uyumlu pozitif kemik sintigrafisi protez enfeksiyonunu düşündürür.…”
Section: Tc-99mi̇şaretlidifosfonatlar(kemiksintigrafisi)unclassified